Crowning the Bihu Queen: Engendering a rural sensibility through reality television. Issue 1 (1st August 2022) - Kheshgi, Rehanna
This article focuses on reality television shows featuring solo female Bihu performance: the music and dance form associated with the Assamese New Year's festival. These shows cultivate a sense of 'reality' by incorporating scenes of finalists on location in their homes. Often depicting hardworking village girls conducting daily chores, these scenes narrate the journey from anonymity to celebrity stardom, highlighting the ability of contestants to embody certain idealized values associated with Assamese womanhood. While judges began embedding these values into Bihu stage competitions in the early 1980s, the scrutiny of individual contestants by celebrity judges has increased since the advent of reality TV Bihu shows in the early 2000s. The success female contestants are able to achieve depends, in part, on their ability to convincingly portray a 'rural' sensibility while maintaining an air of respectability, both as part of Bihu performance and during question-and-answer sessions. Drawing on the author's experience as a guest judge in two seasons of Bihu Rānī ('Bihu Queen'), as well as on interviews with judges, producers, hosts, contestants and session musicians, the article examines how female performers navigate neo-liberal models of competitive performance while maintaining values and beliefs associated with collective ritual performance.